Tomb treasures of the late Middle Kingdom : the archaeology of female burials - Grajetzki, Wolfram (University of Pennsylvania Press, 2014)
Court type burials -- Other burials of women -- Types of jewelry in Late Middle Kingdom burials -- The development of Egyptian burial customs -- The king and the women buried around him.